Delivering the Lee Silverman voice treatment-loud method in-site versus telerehabilitation in people with multiple sclerosis: Feasibility evidence of a non-inferiority pilot randomized controlled trial - Chiara Vitali; Giulia Fusari; Diego Michael Cacciatore; Giulia Smecca; Cinzia Baldanzi; Alessio Carullo; Marco Rovaris; Davide Cattaneo; Francesca Baglio; Sara Isernia (Digital Health)
Objective Telerehabilitation may overcome accessibility barriers related to the Lee Silverman Voice Treatment (LSVT)-Loud for dysphonia rehabilitation in multiple sclerosis (MS). The present study provides the feasibility evidence on patient-relevant structural and procedure effects of a pilot randomized controlled trial comparing LSVT-Loud telerehabilitation (Tele-LSVT-Loud) versus standard delivery. Methods Twenty-one people with MS (six males) with dysphonia were 1:1 randomly allocated to 4 weeks of LSVT-Loud in-site or Tele-LSVT-Loud at home accessing a telemedicine platform. The feasibility of Tele-LSVT-Loud compared to LSVT-Loud was evaluated considering adherence rate, safety (adverse events), technology interaction (User Experience Questionnaire), intrinsic motivation to the treatment (Intrinsic Motivation Inventory), and perceived rehabilitation experience (individual qualitative interviews) during and after the intervention program. Results Thirty-one percent of eligible subjects were unavailable to follow in-site treatment. Drops-outs were higher in the LSVT-Loud than Tele-LSVT-Loud group (4 versus 1). Also, the adherence rate of synchronous sessions was 68.75% in the LSVT-Loud compared to 87.5% in the Tele-LSVT-Loud group, related to greater difficulty in integrating the treatment into a daily routine, as mentioned in the qualitative interview. No relevant adverse events were observed in both groups. The user experience with technology in the Tele-LSVT-Loud group was positive. The interviews revealed a positive therapeutic alliance, regardless of the delivery path. Interestingly, only people in the Tele-LSVT-Loud group judged equivalent the therapist-user relationship in in-site and telerehabilitation settings. Conclusions Telerehabilitation promotes the feasibility of LSVT-Loud. The modality of delivery is a relevant factor in determining eligibility and adherence to a voice rehabilitation program in MS.